Parliamentary volatility in Dáil Éireann – unfreezing the Irish party system? - Domagała, Katarzyna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The article provides an analysis of the phenomenon of parliamentary volatility during three consecutive terms of Dáil Éireann (2007–2011, 2011–2016 and 2016–2020). The study encompasses all personnel changes in the Irish parliament, including party-switching and replacements resulting from the expiration of mandates before the completion of the parliamentary term. To provide a broader context of the analysis, the article includes an overview of the main features of the Irish party system. The study demonstrates that from the perspective of classical systemic analysis, both types of fluctuations did not lead to significant changes in the party system or disrupt parliamentary arithmetic. More than half of the party-switching cases were a consequence of breaking party discipline. However, such formal provisions were not the primary cause of the second type of fluctuation – the expiration of mandates before the completion of the term. Artykuł zawiera analizę zjawiska chwiejności wewnątrzparlamentarnej w trakcie trzech kolejnych kadencji Dáil Éireann (2007–2011, 2011–2016 i 2016–2020). Badanie obejmuje wszystkie zmiany personalne w irlandzkim parlamencie, w tym zmianę afiliacji partyjnej oraz zastępstwa wynikające z wygaśnięcia mandatów przed zakończeniem kadencji parlamentarnej. Aby dostarczyć szerszego kontekstu analizy, artykuł zawiera przegląd głównych cech irlandzkiego systemu partyjnego. Badanie pokazuje, że z perspektywy klasycznej analizy systemowej oba rodzaje fluktuacji nie doprowadziły do istotnych zmian w systemie partyjnym ani nie zakłóciły arytmetyki parlamentarnej. Ponad połowa przypadków zmiany partii była konsekwencją złamania dyscypliny partyjnej. Formalne przepisy regulujące pracę parlamentarzystów nie były główną przyczyną drugiego rodzaju fluktuacji – wygaśnięcia mandatów przed zakończeniem kadencji.
Niestabilność parlamentarna w Dáil Éireann – odmrożenie irlandzkiego systemu partyjnego?
Keywords: party-switching; replacement; Ireland; intraparliamentary volatility; Irish party system; zmiany afiliacji partyjnych; wygaśnięcia mandatów; chwiejność wewnątrzparlamentarna; system partyjny Irlandii